The Influence of Color in Soteria Bandung Recovery House on the Therapy and Recovery Process - Caitlyn; Darmayanti, Tessa Eka (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
This article discusses the selection of the right color to be applied in a recreation and rehabilitation place spesifically designed for individuals with mental disorders. The use of color in a room plays an important role in shaping an individual's mood, emotions, and psychology. In the context of a recreation and rehabilitation place for people with mental disorders, the selection of the right color can be one of the strategic elements to create an environment that supports recovery and improves their quality of life. A recreation and rehabilitation place for them not only functions as a treatment room, but also as a place to improve holistic well-being. The purpose of this study was to determine the role of color in recreation and rehabilitation places in the psychological effects felt by people with mental disorders. Using qualitative methods and using a color psychology approach, this study explores how certain colors can affect mood, reduce stress, increase relaxation, and support the healing process. In this case, design elements, including color, are an important part of supporting therapy and creating a positive atmosphere. In addition, it is also expected to provide new knowledge about the influence of color in the Soteria recovery house on the recovery process of patients with mental health disorders.